A novel SERS platform based on flower-like Bi2WO6-GO for the quantification of sepsis-associated biomarker procalcitonin - Sitong Li; Rui Lan; Qing Liu; Yang Tian; Tingting Zheng (Advanced Sensor and Energy Materials, 2024)
Procalcitonin (PCT) is a promising biomarker for identification of the origin and severity of sepsis, which is a deadly body infection. However, traditional diagnostic tools exhibited challenges in complicated instruments, sensitivity and time consuming. Herein, we created a highly sensitive and selective surface-enhanced Raman scattering (SERS) platform for PCT monitoring based on flower-like Bi2WO6-graphene (Bi2WO6-GO), which was created as a chemical mechanism (CM)-based SERS substrate with high stability as well as a remarkable enhancement factor (EF) value of 2.07 × 108. The high EF value was primarily attributed to the efficient charge transfer (CT) between Bi2WO6-GO and 4-(2-(3-(dicyanomethylene)-5,5-dimethylcyclohex-1-en) vinyl) phenyl) boronic acid (BP) as a Raman reporter. The BP molecule was designed to play double key roles as a Raman reporter as well as a recognition probe. Owing to the specially designed BP molecule recognition of PCT and the high SERS effects of BP on Bi2WO6-GO, the developed SERS platform was employed for ultrasensitive and selective PCT quantification with a limit of detection down to 0.31 pg/mL in less than 8 min. The developed platform was also successfully utilized for early monitoring in sepsis rats, demonstrating practical potential for pathogene screening.